The effect of blended learning models on ESL students' self-efficacy and proficiency - Zalina Mohd Zamri; Suthagar Narasuman (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Malaysian government has encouraged educational institutions to incorporate digital technology and internet resources in the classroom for the past decade. This call was materialised by incorporating various models of blended learning in institutions of higher learning. This was also a value-added method for ESL learners and instructors to enhance students' proficiency and self-efficacy in mastering listening, speaking, reading and writing skills. The objective of the present study is to ascertain the relationship between blended learning and students' self-efficacy in improving their proficiency in the English language. The respondents in this study are diploma-level college students in a public higher-learning institution. The study employed an experimental design involving control and experimental groups. Students in the experimental groups were exposed to a series of blended learning lessons, while students in the control group were taught using traditional lessons. Data was collected by administering the Learning English Self-Efficacy Survey and English Proficiency Test. Data analysis revealed a positive relationship between blended learning, self-efficacy in English language learning and proficiency.